Cohesive Devices in EFL Students' Essays and Problems Encountered during Writing - Zahara, Rita; Yusuf, Yunisrina Qismullah; Samad, Iskandar Abdul; Singh, Charanjit Kaur Swaran (Universitas Jambi, Indonesia, 2023)
The research investigated the cohesive devices used in EFL students' recount texts and the problems encountered during their writing. 33 high school students' essays were analyzed, and the students were interviewed. The findings showed that all five types of cohesive devices appeared in the students' writings, with reference the most, followed by a conjunction, lexical cohesion, ellipsis, and substitution the least. Three types of cohesive devices were identified as problematic to the students: conjunction, reference, and lexical cohesion. Four reasons were further found for the students' difficulty in using the cohesive devices: pure error, absence of knowledge, overuse, and lack of writing practice. These findings may give new insights for language teachers in the attempt to understand the causes that lead to cohesion problems in students' writing so that proper measures can be taken to address them and improve the quality of their writing generally.